Effect of acetylsalicylic acid on platelet activation and oxidative profile in a set of Brazilian patients with type 2 diabetes mellitus. Issue 2 (March 2015) - Duarte, Rita C.F.; Gonçalves, Líllian H.; Campos, Fernanda M.F.; Filho, Olindo A.M.; Alves, Michelle T.; Fernandes, Ana P.; Borges, Karina B.G.; Dusse, Luci M.S.; Faria, Mayara C.; Gonçalves, Gisele S.; Bosco, Adriana A.; Sandrim, Valéria C.; et al.
<x xml:space="preserve">Abstract</x> Type 2 diabetes mellitus (DM2) is a metabolic disorder associated with hyperactivation of platelets, increased formation of platelet microparticles (PMPs) and oxidative stress that are related to cardiovascular complications. Acetylsalicylic acid (ASA) is an antiplatelet agent used in the prevention of atherothrombosis. The aim of this study was to evaluate the effect of ASA by means of platelet activation and oxidative profile. We collected blood samples of 81 patients with DM2 before and during ASA treatment. These samples were analyzed to determine the levels of 2, 3-dinor thromboxane-B2 (2, 3-dinor-TXB2), PMPs, thiobarbituric acid reactive species (TBARS) and 3-(4, 5-dimethylthiazol-2yl)-2, 5-diphenyltetrazolium bromide (MTT). Moreover, the relationship between the levels of 2, 3-dinor-TXB2 with some clinical and laboratory variables such as glycated hemoglobin, platelet count, D dimer, low-density lipoprotein cholesterol and glycoprotein IIb/IIIa and cyclooxygenase-1 polymorphisms was evaluated. ASA intake did not change the levels of PMP, TBARS and MTT. Although a significant decrease in the levels of 2, 3 dinorTXB2 (P < 0.001) in patients under ASA has been observed, an equal and satisfactory response to this drug was not found. However, the presence of PIA2 allele in GPIIIa gene may be associated with a better response to ASA intake in these patients, whereas other clinical and laboratory variables showed no association with this drug use. These findings are consistent with previous reports in the literature that patients with DM2 do not benefit in an equal way from the use of ASA for primary prevention of atherothrombotic events.